Design and Simulation of Closed Loop Proportional Integral (PI) Controlled Boost Converter and 3-phase Inverter for Photovoltaic (PV) Applications - Kadhim, Riadh Adnan (Al-Khwarizmi Engineering Journal, 2019)
This research deals with the design and simulation of a solar power system consisting of a KC200GT solar panel, a closed loop boost converter and a three phase inverter by using Matlab / Simulink. The mathematical equations of the solar panel design are presented. The electrical characteristics of the panel are tested at the values ​​of 1000 for light radiation and 25 °C for temperature environment. The Proportional Integral (PI) controller is connected as feedback with the Boost converter to obtain a stable output voltage by reducing the oscillations in the voltage to charge a battery connected to the output of the converter. Two methods (Particle Swarm Optimization (PSO) and Zeigler- Nichols) are used for tuning PI controller to enhance the overall performance of the system. The Sine Pulse Width Modulation (SPWM) technique was used to obtain a pure 3-phase in low distortion. The voltage and current output values ​​of ± 14V and ± 2.8A are obtained, and the Total Harmonic Distortion (THD) value is 4.20%.